PENGEMBANGAN BAHAN AJAR BERBASIS MAJALAH ANAK UNTUK MENINGKATKAN LITERASI SAINS PADA MATA PELAJARAN IPAS SISWA KELAS V SDN PASIRSARI 01 - Surtijah, Endeh; Barokah, Awalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a children’s magazine-based teaching material for the Natural and Social Sciences (IPAS) subject with the theme “The Secrets of Our Body” to improve science literacy among fifth-grade students at SDN Pasirsari 01. The development model used was ADDIE (Analyze, Design, Develop, Implement, Evaluate), with one fifth-grade class as the research subject. Data collection instruments included observation, interviews, questionnaires, as well as pretest and posttest science literacy assessments. Validation results from subject matter experts, media experts, and the class teacher indicated that the product was in the “Highly Feasible” category for use in learning. Classroom implementation showed positive responses from both teachers and students, with students displaying greater enthusiasm, active participation in discussions, and engagement in learning activities. Science literacy test results indicated a significant increase in posttest scores compared to pretest scores, with an N-gain improvement category of moderate/high. This study concludes that a children’s magazine can serve as an effective, engaging, and contextual alternative teaching material to enhance science literacy among elementary school students. Keywords: teaching materials, children’s magazine, science literacy